Moving from decision to action in conservation science. (September 2020) - Wright, Alexander D.; Bernard, Riley F.; Mosher, Brittany A.; O'Donnell, Katherine M.; Braunagel, Taylor; DiRenzo, Graziella V.; Fleming, Jill; Shafer, Charles; Brand, Adrianne B.; Zipkin, Elise F.; Campbell Grant, Evan H.
Abstract: Biodiversity loss is a major threat to the integrity of ecosystems and is projected to worsen, yet the path to successful conservation remains elusive. Decision support frameworks (DSFs) are increasingly applied by resource managers to navigate the complexity, uncertainty, and differing socio-ecological objectives inherent to conservation problems. Most published conservation research that uses DSFs focuses on analytical stages (e.g., identifying an optimal decision), making it difficult to assess and learn from previous examples in a conservation practice context. Here, we (1) evaluate the relationship between the application of decision science and the resulting conservation outcomes, and (2) identify and address existing barriers to the application of DSFs to conservation practice. To do this, we develop a framework for evaluating conservation initiatives using decision science that emphasizes setting attainable goals, building momentum, and obtaining partner buy-in. We apply this framework to a systematic review of amphibian conservation decision support projects, including a follow-up survey of the pertinent conservation practitioners, stakeholders, and scientists. We found that all projects identified optimal solutions to reach stated objectives, but positive conservation outcomes were limited when implementation challenges arose. Further, we identified multiple barriers (e.g., dynamic and hierarchical leadership, scale complexity, limited resource availability) that can inhibit the progression from decision identification to action implementation (i.e., 'decision-implementation gap'), and to successful conservation outcomes. Based on these results, we provide potential actionable steps and avenues for future development of DSFs to facilitate the transition from decision to action and the realization of conservation successes. Highlights: Decision support frameworks are an avenue to address complex conservation problems. Evaluation of their use can lead to evidence-based insights and future development. Implementation challenges limit positive outcomes – 'decision-implementation gap'. There are actionable steps to further improve the use of decision science.